Método multirresíduo de agrotóxicos em caqui empregando QuEChERS sem limpeza do extrato e UHPLC-MS/MS - Rocha, Graziela Iop (2022)
Pesticides are widely used in food crops and residues of these compounds may be present in these crops. Despite their large-scale use in agriculture, pesticides can be dangerous to human health, animals and the environment. These risks arising from the frequent use of pesticides demand the establishment of adequate analytical methods, as well as monitoring programs to assess compliance with the maximum amount of pesticide residues that may be present in food, called maximum residue limits (MRLs). Persimmon is a fruit widely consumed in nature and sometimes used in the production of by-products. Persimmon production stands out in Brazil, appearing in recent years among the twenty most produced fruits. The state of São Paulo is the leader in production, but the state of Rio Grande do Sul has been increasing persimmon production, being the second state that produces the most. The export volume of the fruit is also high. There are numerous varieties of persimmon, which is a very sensitive fruit, with a short harvest period and has conservation problems, resulting in widespread use of pesticides. The simultaneous determination of pesticides of different classes in different matrices is quite complex, so the use of a multiresidue method is essential. The QuEChERS method has been shown to be very efficient for these cases, and allows several modifications according to the characteristics of the matrices. Thus, the work aimed to develop and validate a fast and efficient sample preparation method using QuEChERS for multiresidue determination of pesticides in persimmon by ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). Modifications were made to the original QuEChERS method, such as replacing the extract cleaning step with just a higher dilution of the extract before analysis. This innovation generates a simpler, faster and cheaper analysis. The modified QuEChERS method was validated for 86 pesticides and the method limit of quantification (LOQ), confirmed by recovery assays, ranged from 10 to 40 μg kg-¹, recovery levels were between 70 and 120% and RSD ≤ 20%. The matrix effect was ±20% for all compounds. The analyzes by UHPLC-MS/MS with ionization by electrospray showed high selectivity, sensitivity and detectability. The validated method was applied to commercial samples of persimmon and residues of five pesticides were found, some of them banned in the country, such as carbendazim and dimethoate. In this way, the results obtained showed that the proposed method is efficient and can be used routinely for the multiresidue determination of pesticides in persimmon